Association between bicarbonate levels and mortality among acute respiratory distress syndrome patients: An analysis based on Medical Information Mart for Intensive Care database. - Junli Han; Lianghe Wang; Lingling Jin; Mingzhu Liu (PLoS ONE)
Objective This study explored the association between serum bicarbonate levels and mortality risk among patients with acute respiratory distress syndrome (ARDS) admitted to the intensive care unit (ICU). Methods This was a retrospective cohort study utilizing data extracted from the Medical Information Mart for Intensive Care (MIMIC)-IV database. Cox proportional hazards models and restricted cubic splines (RCS) were deployed for elucidating the association between the baseline bicarbonate levels and the risk of 28-day mortality while utilizing the Kaplan-Meier method to estimate survival curves, with hazard ratio (HR) and 95% confidence interval (CI). Subgroup analyses were conducted based on age, gender, Charlson Comorbidity Index (CCI) score, ARDS severity and bicarbonate administration. Results Totally, 6,377 patients (15.38% deaths) were included. Baseline bicarbonate was significantly associated with 28-day mortality (HR: 0.98, 95% CI: 0.97-1.00, P = 0.011) in patients with ARDS. This association was particularly evident in female patients (HR: 1.16, 95% CI: 1.14-1.87, P = 0.003), those with a CCI of 2 or higher (HR: 1.27, 95% CI: 1.05-1.53, P = 0.013), among those with a PaO2/FiO2 ratio ranging from 200 to 300 mmHg (HR: 1.39, 95% CI: 1.08-1.78, P = 0.011), and those without bicarbonate administration (HR = 1.26, 95%CI: 1.07-1.48, P = 0.004), where bicarbonate levels falling below 23 mEq/L were linked to a heightened risk of not surviving the first 28 days in ARDS patients. RCS analysis revealed that the bicarbonate levels were non-linear associated with the 28-day mortality in ARDS patients (P for non-linear <0.001). Conclusion Lower serum bicarbonate levels are significantly associated with an increased 28-day mortality risk in ARDS patients, with particular emphasis on female patients, those with higher CCI scores, and those with milder ARDS. Baseline bicarbonate levels of ARDS patients in ICU have certain clinical reference value for the development of clinical management and the assessment of prognostic risk during the ICU admission.